2021
DOI: 10.1108/tr-05-2020-0209
|View full text |Cite
|
Sign up to set email alerts
|

Market knowledge impacts on product and process innovation: evidence from travel agencies

Abstract: Purpose The purpose of this paper is to examine the relationship between the attributes of market knowledge (depth/breadth) and particular types of (process/product) innovation. The mediating mechanism of ambidextrous (exploratory/exploitative) capabilities is also investigated. Design/methodology/approach Data from 153 travel agencies from two phases of data collection in Taiwan were analyzed using the structural equation modeling method. Findings Market knowledge depth directly and positively impacts pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…In other words, external and internal networks jointly improve KC. These findings support previous research, which, though not directly focusing on KC, found that network capability ambidexterity improves KC to further innovation performance (Zheng, 2018; Chen et al , 2021). Thus, network capabilities have been considered important antecedents of KC (Zhou et al , 2016).…”
Section: Discussionsupporting
confidence: 91%
“…In other words, external and internal networks jointly improve KC. These findings support previous research, which, though not directly focusing on KC, found that network capability ambidexterity improves KC to further innovation performance (Zheng, 2018; Chen et al , 2021). Thus, network capabilities have been considered important antecedents of KC (Zhou et al , 2016).…”
Section: Discussionsupporting
confidence: 91%
“…The first theoretical implication may be that the positive relationship between enterprise knowledge and innovation performance confirms findings that all knowledge from different acquisition channels can improve innovation performance [76]. While previous investigations on how knowledge affects innovation performance have mostly focused on knowledge attributes [40] and state of knowledge [77], this study focused on knowledge acquisition channels and examined the positive effects, enriching the existing research on the impact of enterprise knowledge on innovation performance.…”
Section: Theoretical Implicationsmentioning
confidence: 70%
“…In the existing studies, scholars mostly divide external knowledge acquisition into market knowledge and technical knowledge acquisition [39]. On the one hand, market knowledge is the basic requirement of modern innovation, and enterprises can acquire external market knowledge through effective interaction and in-depth communication with consumers, suppliers, or other external partners, so as to correctly and efficiently respond to the complex demands of different customers and markets [40]. At the same time, the act of acquiring external market knowledge also releases positive signals to the outside world, promoting the investment behavior of external partners and providing more resources for innovation behavior, thus enhancing innovation performance.…”
Section: Hypothesis 1a (H1a)mentioning
confidence: 99%
“…Specifically, the link between input innovation and destination innovativeness lends support to the resource-based view on innovation, which examines innovation capacity as bundles of interrelated resources and the process used to leverage innovation resources (Terziovski, 2010). Product innovation also plays a significantly important role in encouraging perceived destination innovativeness (Chen et al , 2022), a result that highlights the central role of differentiation and “step-out” products in predicting a destination image as original and distinctive (Hubert et al , 2017). The results are different from those of prior studies suggesting that the remaining process, marketing and management innovations significantly influence perceived innovativeness (Ardi, 2020).…”
Section: Discussionmentioning
confidence: 99%